2021
DOI: 10.11113/ijic.v11n2.321
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Machine Learning Algorithms for Sentiment Analysis of Bangla Newspaper

Abstract: We can state undoubtedly that Bangla language is rich enough to work with and implement various Natural Language Processing (NLP) tasks. Though it needs proper attention, hardly NLP field has been explored with it. In this age of digitalization, large amount of Bangla news contents are generated in online platforms. Some of the contents are inappropriate for the children or aged people. With the motivation to filter out news contents easily, the aim of this work is to perform document level sentiment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…And their performance evaluation showed that LS-TWSVM is the best of all three with 92.96% accuracy. Maisha et al [7] perform sentiment analysis on Bangla news using "pipeline" class along with six state-of-the-art supervised ML algorithms which includes decision tree (DT), multinomial naive Bayes (MNB), k-nearest neighbor (KNN), logistic regression (LR), random forest (RF) and lagrangian support vector machine (LSVM). Random forest algorithm out stands all other algorithms securing 98% accuracy in percentage split method.…”
Section: Introductionmentioning
confidence: 99%
“…And their performance evaluation showed that LS-TWSVM is the best of all three with 92.96% accuracy. Maisha et al [7] perform sentiment analysis on Bangla news using "pipeline" class along with six state-of-the-art supervised ML algorithms which includes decision tree (DT), multinomial naive Bayes (MNB), k-nearest neighbor (KNN), logistic regression (LR), random forest (RF) and lagrangian support vector machine (LSVM). Random forest algorithm out stands all other algorithms securing 98% accuracy in percentage split method.…”
Section: Introductionmentioning
confidence: 99%